1949
DOI: 10.1182/blood.v4.11.1256.1256
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Mean Corpuscular Volume and Reticulocytosis in Phenylhydrazine Anemia in Swine

Abstract: 1. Six adult swine were given phenylhydrazine hydrochloride orally and intravenously. Hematologic observations, which included periodic bone marrow studies were made before, during, and after the administration of the drug. 2. Five swine responded to the drug in the usual manner with progressive anemia, reticulocytosis, and erythrocytic hyperplasia of the bone marrow. Three animals died between the thirty-ninth and fiftieth day of the experiment after receiving a total dose of 0.30 to 0.35 Gm. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1954
1954
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although benzene has not been identified as the metabolite of phenylhydrazine (Mclsaac et al, 1958) or its derivatives (Colvin, 1969;Juchau and Horita, 1972), Lawrason et al (1949) observed symptoms typical of benzene poisoning from treatment of swine with phenylhydrazine. Beaven and White (1954) identified benzene as the end product of phenylhydrazine or acetylphenylhydrazine incubation with oxyhemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Although benzene has not been identified as the metabolite of phenylhydrazine (Mclsaac et al, 1958) or its derivatives (Colvin, 1969;Juchau and Horita, 1972), Lawrason et al (1949) observed symptoms typical of benzene poisoning from treatment of swine with phenylhydrazine. Beaven and White (1954) identified benzene as the end product of phenylhydrazine or acetylphenylhydrazine incubation with oxyhemoglobin.…”
Section: Discussionmentioning
confidence: 99%